Retrospective study of musculoeskeletal pathologies in dogs at a Veterinary Hospital in Chile, from 2014 to 2017 - Fischer Wiethuchter, Christof (2020)
A retrospective study of musculoskeletal pathologies in dogs was carried out at the German Kleintierklinik Veterinary Center in the city of San Pedro de la Paz, Chile, in the period September 2014 - June 2017. Of the total of 2000 clinical files analysed, 144 were related to patients with a problem in the musculoskeletal system. The musculoskeletal pathologies with the highest incidence were fractures (40, 27.8%), patellar dislocation (31, 21.5%), rupture of the cranial cruciate ligament (25, 17.4%) and hip dysplasia (23, 15.8%). Males, purebreds, and adults were significantly more affected by musculoskeletal pathologies.